NLRP3 inflammasome priming: A riddle wrapped in a mystery inside an enigma - McKee, Chloe M.; Coll, Rebecca C. (Journal of leukocyte biology, 2020)
The NLRP3 (NOD‐, LRR‐, and pyrin domain‐containing protein 3) inflammasome is an immunological sensor that detects a wide range of microbial‐ and host‐derived signals. Inflammasome activation results in the release of the potent pro‐inflammatory cytokines IL‐1β and IL‐18 and triggers a form of inflammatory cell death known as pyroptosis. Excessive NLRP3 activity is associated with the pathogenesis of a wide range of inflammatory diseases, thus NLRP3 activation mechanisms are an area of intensive research. NLRP3 inflammasome activation is a tightly regulated process that requires both priming and activation signals. In particular, recent research has highlighted the highly complex nature of the priming step, which involves transcriptional and posttranslational mechanisms, and numerous protein binding partners. This review will describe the current understanding of NLRP3 priming and will discuss the potential opportunities for targeting this process therapeutically to treat NLRP3‐associated diseases. Describes the complex NLRP3 priming process and how it might be targeted to treat NLRP3‐associated diseases.